Development of water insecurity scale for rural households in Cameroon- Central Africa - Carole Debora Nounkeu; Kenneth J. Gruber; Joseph Kamgno; Ismael Teta; Jigna Morarji Dharod (Taylor & Francis Group, 2021)
Background: Water represents the core of food-energy nexus and is vital for human survival. In developing countries, contaminated water and lack of basic water services undermine efforts to improve nutritional status and related health issues. In the rural areas of Central Africa, a majority of the population lacks access to improved water sources and has to devote considerable efforts to obtain water. Objectives: Using the following definition of water insecurity, i.e. it exists when access to adequate amount of safe and clean water does not occur all the times for the entirety of household members to lead a healthy and active life, the study aimed to develop and test a household-level experiential water insecurity scale for rural households in Central Africa. Methods: The research was conducted in three phases: 1) the formative data collection; 2) the scale development; and, 3) the scale testing. In the third Phase, the scale was tested with 250 women who were water managing person of their households. Statistical analysis included items reduction, reliability, as well as criterion and construct validity assessment. The testing led to a final scale of 17 statements (WATINE-17), covering three domains of water insecurity: 1) psychosocial distress; 2) quantity; 3) quality of water. Results: The scale showed an excellent reliability (Cronbach's alpha = 0.92) and was significantly associated with lower frequency of water intake among women (p = 0.007, concurrent validity). In assessing WATINE-17's predictive validity, it was found that water insecurity was positively related to food insecurity (p < 0.001) and the level of water insecurity was the highest among severely food insecure households [F (3, 246) = 22.469, p < 0.001]. Conclusion: The WATINE-17 is able to capture key elements of water insecurity and can be used to monitor and evaluate SDG# 6 and water-related programs, such as WASH, in Central Africa.